АКАДЕМИЯЛЫҚ ЛИЦЕЙЛЕРДЕ Ө.ХОЖАНИЯЗОВ ДӨРЕТИЎШИЛИГИН ОҚЫТЫЎ - Алламбергенов, К.; Юсупов, Қ.А. (SCIENCE and SOCIETY, 2020)
The article deals with individual peculiarities of the creative work of the famous Karakalpak writer U.Khojaniyazov and his skill as an artist of a word.
Keywords: literature; specialist in literature; poetry; poem; character; creative work; style; method; writing; genres; language; publicistic